A Framework for Finding and Interpreting Stellar CMEs. Issue Volume 12:Issue S328(2016) (12th September 2017) - Osten, Rachel A.; Wolk, Scott J.
Abstract: The astrophysical study of mass loss, both steady-state and transient, on the cool half of the HR diagram has implications both for the star itself and the conditions created around the star that can be hospitable or inimical to supporting life. Stellar coronal mass ejections (CMEs) have not been conclusively detected, despite the ubiquity with which their radiative counterparts in an eruptive event (flares) have been. I will review some of the different observational methods which have been used and possibly could be used in the future in the stellar case, emphasizing some of the difficulties inherent in such attempts. I will provide a framework for interpreting potential transient stellar mass loss in light of the properties of flares known to occur on magnetically active stars. This uses a physically motivated way to connect the properties of flares and coronal mass ejections and provides a testable hypothesis for observing or constraining transient stellar mass loss. Finally I will describe recent results using observations at low radio frequencies to detect stellar coronal mass ejections, and give updates on prospects using future facilities to make headway in this important area.